A new genus Socifera gen. nov. of Argyresthiidae (Lepidoptera: Yponomeutoidea) from Hainan Island, China - Liu, Tengteng; Li, Houhun (Zootaxa, 2022)
A new genus Socifera gen. nov. of Argyresthiidae is established. The diagnostic characters against Argyresthia Hübner, [1825] are listed. Socifera is endemic to Hainan, a tropical island in southern China. The type species Socifera asymmetra Liu & Li, sp. nov. is described. The adult, venation, abdominal structures, male and female genitalia are illustrated.